The Intersection Of Nursing And Public Health: Addressing Community Needs (Journal of Namibian Studies : History Politics Culture, 2022)
The intersection of nursing and public health represents a critical synergy in addressing community health needs. This abstract explores the multifaceted roles of nurses in public health, including community health education, disease surveillance and outbreak response, and healthcare policy advocacy. Through their expertise and compassion, nurses contribute significantly to improving population health outcomes and reducing health disparities. A case study focusing on nurses' response to the COVID-19 pandemic illustrates their pivotal role in addressing community needs.